THE APPLICATION OF LEARNING PROCESS AND PORTFOLIO ASSESSMENT BASED ON MULTIPLE INTELLIGENCE TO ENHANCE STUDENTS' MASTERY ON HUMAN CIRCULATORY SYSTEM - Lita Kumalasari, - (2018)
The purpose of this study is to examine the application of learning process and portfolio assessment in the teaching and learning of Biology in a Bandung private school. The portfolio assessment was given in some learning activities to compliment the learning process based on Multiple Intelligence Theory approach for a lesson human circulatory system. This study starts with a test test by using MI test based on Howard Gardner's MI model to see their dominant intelligence. The result showed the percentage of top three ranks of intelligence are Bodily-Kinesthetic (73%), Visual-Spatial (68%), and Interpersonal (66%). The learning process is given by using some different multimedia and activities to engaged their learning style and intelligence such as mini experiment, short clip, and questions. The students was assessed during the learning activities for completed their portfolios. Post-test was given after the learning process for checking their understanding toward the lesson and N-gain obtained is 0,51 which is in the range of 0,7> g>0,3 with interpretation of concept mastery in catergory medium. At the end of the study, it is reveal that the students who are learned by Multiple Intelligence instructional approach have more enhance to the lesson given. It's also found out that the students participated in the learning process which Multiple Intelligence approach was applied enjoyed the activities and have great fun.